Estimating Paddy Field Water Requirements Using CROPWAT 8.0: A Case Study in Batang Anai Irrigation Area, West Sumatra, Indonesia - Syahlevi, Sutan Ikhsan; Nurhamidah; Junaidi (BRIN Publishing, 2024)
The accurate estimation of crop water requirements is critical for efficient water resource management, particularly in regions with limited irrigation resources. This study aims to evaluate the water requirements for rice crops using the CROPWAT 8.0 model and compare the results with the Penman Modification Calculation method, as specified in the Irrigation Planning Standards (KP-01). This research is conducted using climatological data from the Kandang IV Station located near Batang Anai Irrigation area, focusing on key factors such as effective precipitation, air temperature, humidity, wind speed, sunshine duration, and topography. The representative Soil of the local area was incorporated into the analysis. The study finds that the average evapotranspiration (ETo) using CROPWAT 8.0 was 3.09 mm/day, with the peak water demand for rice occurring at the end of August, reaching 1.51 L/s·ha. These findings align with the study’s objective of assessing irrigation demand for rice crops and offer a comparison of methodologies used to estimate water requirements. The results emphasize the need for improvements in the default crop and soil data used by CROPWAT 8.0 to better align with local agricultural conditions in Indonesia. This study contributes to the ongoing development of more accurate models for water requirement estimation and highlights the importance of region-specific calibration in irrigation planning. Further research is needed to enhance the model's functionality and to explore alternative methods for improving water use efficiency in rice farming.